Lack of Family Planning is an Avoidable Cause of Maternal and Child Death in Uganda - Mubangizi, Vincent (BMJ Glob Health, 2016)
Reduction of maternal and child mortality is universally accepted as a desirable goal. However, the same is not true for family planning. In Uganda, a developing country with high maternal and child deaths, 12% of pregnancies are unwanted, 44% unplanned and 32% mistimed. We used confidential enquiry to identify avoidable factors, without blaming anyone. In the UK, confidential enquiries have helped to address avoidable factors in the health system and beyond which have contributed to deaths. This paper examines whether promotion of family planning would be accepted as an intervention to prevent maternal and child deaths.
Keywords: Maternal and child mortality; Family planning; Child deaths; Pregnancies; Uganda